Two-staged Correction of Severe Congenital Scoliosis Associated With Intraspinal Abnormalities. Issue 8 (October 2016) - Zhang, Zhenxing; Hui, Hua; Liu, Tuanjiang; Zhang, Zhenping; Hao, Dingjun
Abstract : Study Design: A retrospective study. Objective: To analyze the efficacy and safety of perioperative halo-gravity traction as an adjunct to posterior vertebral column resection (PVCR) in the treatment of patients with severe congenital scoliosis and coexisting asymptomatic intraspinal pathologies (diastematomyelia and/or tethered cord). Summary of Background Data: Few reports to our knowledge review the use of perioperative halo-gravity traction and PVCR in this patient population. Materials and Methods: A total of 17 patients with a minimum 2-year follow-up who underwent PVCR using perioperative halo-gravity traction were analyzed. Patients were analyzed by age at date of examination (range, 11–23 y; mean, 14.4 y), sex (7 male, 10 female), major coronal curve magnitude (range, 108–149 degrees; average, 125 degrees), major sagittal curve magnitude (range, 72–118 degrees; average, 91 degrees). Complications related to halo traction and PVCR were reviewed. Results: Radiographic outcomes demonstrated Cobb angle of major curve had an average correction of 28% after halo traction and it measured 53 degrees (range, 42–84 degrees) at the last follow-up, for a 58% correction. Maximal kyphosis improved to 58 degrees (range, 43–76 degrees) at ultimate follow-up. There were no permanent neurological deficits in this series. Conclusions: The study results suggested that surgical treatment for intraspinal abnormality may be unnecessary in asymptomatic patients with severe congenital scoliosis who are undergoing scoliosis corrective surgery. PVCR combined with perioperative traction is a safe and effective alternative for such patients.